A Review Model Of Pailit Decision By The Niaga Court - Muhammad Edwin Syahputra Lubis; Henry Aspan; Tamaulina Br. Sembiring (SEAN Institute, 2023)
Bankruptcy law in Indonesia is regulated by Undang-Undang Nomor 37 Tahun 2004. Bankruptcy occurs when a debtor is unable to pay their overdue debts. A bankruptcy court decision results in a public seizure of the debtor's entire estate. In Case Nomor 2/Pdt.Sus-Pailit/2018/Pn.Niaga.Mdn, PT. Tri Murti Perkasa and Hotmaulin Simare-Mare, filed a bankruptcy petition against PT. Pro Mekanika Indonusa. The second petitioner also claims a debt from the company. The judge ruled for bankruptcy against PT. Pro Mekanika Indonusa, and Balai Harta Peninggalan (BHP) Medan was appointed as the Curator. Legal consequences of bankruptcy include the debtor losing control over their assets, the appointment of a supervising judge and curator, and the judge deciding on costs. The legal process must meet legal requirements and consider juridical, philosophical, and sociological considerations. To enhance the efficiency of the bankruptcy process, it is necessary to revise bankruptcy legal regulations, supervising judges and curators must maintain transparency, and the panel of judges must carefully examine evidence to avoid baseless lawsuits.